Magnesium and Zinc as Vital Micronutrients Enhancing Athletic Performance and Recovery - a Review - Rafal Kaczorowski; Tomasz Forenc; Jaromir Hunia; Julia Górny; Michał Janiszewski; Jonasz Jurek; Marcin Komorowski; Alicja Kapciak; Aleksandra Pelczarska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Aim of the Review Magnesium and zinc are vital for cellular metabolism and maintaining homeostasis, playing a particularly significant role for athletes. Magnesium, which is largely stored in bones and muscles, is essential for protein synthesis. Zinc, a critical trace element found in muscle and bone tissue, participates in over 300 enzymatic reactions, acts as an antioxidant and making both minerals crucial for physical performance. This study aims to explore the physiological role of magnesium (Mg) and zinc (Zn) in the context of athletic performance and to examine their impact on energy metabolism, muscle function, protein synthesis and potential benefits of Mg and Zn supplementation for improving athletic outcomes and post-exercise recovery. Methods A comprehensive review of scientific literature was conducted through a thorough search of the PubMed database to explore the latest findings on the utility of magnesium and zinc in sports. Only articles in English were considered. Current Knowledge The review results indicate that Mg and Zn play critical roles in energy metabolism, muscle and immune system health. Mg deficiency can impair muscle function and reduce endurance, while its supplementation supports muscle relaxation, cardiovascular health, and respiratory efficiency. Although required in small amounts, Zn is indispensable for enzymatic activity, protein synthesis, hormonal balance, and muscle recovery, making it vital for post-exercise recovery and immune response modulation. Conclusions Available data suggest that Mg and Zn supplementation may positively influence athletic performance, energy metabolism, and recovery post-exercise, though further research is needed to establish specific supplementation guidelines. This review provides a foundation for developing supplementation strategies aimed at enhancing athletic performance and supporting healthy recovery.